Evaluation of the health knowledge of the students of the concentrated program in health instruction at the Eulogio Rodriguez Jr. High School - Guadiz, Lina Llamas 1944- (s.n.], 1973)
This paper analyzed the health knowledge of fourth year students enrolled in the concentrated and non-concentrated programs in health education at the Euologio Rodriguez Jr. High School, Pilot School in health education during their first and second years. This study eventually determined the effect of the concentrated health instruction program in terms of the health knowledge of the students.